Cystinuria caused by a SLC7A9 missense mutation in Siamese-crossbred litter mates in Germany - Hilton, Stephanie; Mizukami, Keijiro; Giger, Urs (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2017)
Cystinuria is caused by defective proximal renal tubular reabsorption of the amino acids cystine, ornithine, lysine, and arginine (COLA). The low solubility of cystine in mildly acidic urine may lead to the formation of urinary cystine crystals and uroliths. Much progress has been made recently in the diagnosis and understanding of cystinuria in companion animals. In cats, cystinuria affects equally both genders independent of neutering status and, despite being rare, already more cystinuria-causing mutations have been detected in cats compared to dogs. In this study a litter of Siamese-crossbred cats in Germany was assessed clinically for cystinuria and screened for mutations known to cause cystinuria in cats. An adult male castrated cat was presented with cystine crystalluria and calculi-related urinary obstruction and treated with perineal urethrostomy, cystotomy, and medical management. This cat and a neutered male littermate without evidence of urinary tract disease were found to be positive for cystine by urinary nitro prusside test, to have increased urinary COLA values and to be homozygous for the p.Val294Glu mutation in the SLC7A9 gene coding for b0,+AT subunit of the b0,+ renal COLA transporter. Another littermate was non-cystinuric and did not carry this mutation. The same SLC7A9 mutation was previously found in a Maine coon, a Sphinx and a medium-haired cat in North America suggesting a common ancestor and likely first widespread SLC7A9 mutation causing cystinuria in cats. Genetic screening for this mutation may offer a simple and precise mean to diagnose other cats for cystinuria and offer specific management.
Keywords: Feline; cystine; urolithiasis; COLA; tiopronin